2023
DOI: 10.1101/2023.11.28.569056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Cytokine and Coronavirus Nucleocapsid Protein Interactivity Using Large-Scale Virtual Screens

Phillip J. Tomezsko,
Colby T. Ford,
Avery E. Meyer
et al.

Abstract: In the battle against the ever-changing SARS-CoV-2 landscape, understanding the interactions between viral proteins and the human immune system is paramount as it helps to explain potential factors contributing to diverse immunological responses in infected individuals. In this study, we employed state-of-the-art molecular docking tools to conduct large-scale virtual screens, predicting the binding affinities between 64 human cytokines against 17 coronavirus nucleocapsid proteins. Our comprehensivein silicoana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…To complete the 42 docking experiments, this took approximately 3 hours on ten 36-core nodes. This scalable docking process closely follows methods reported in Tomezsko and Ford et al 2023 (32) and the published antibody docking protocol from the Bonvin Lab at Utrecht University (30, 33, 34).…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…To complete the 42 docking experiments, this took approximately 3 hours on ten 36-core nodes. This scalable docking process closely follows methods reported in Tomezsko and Ford et al 2023 (32) and the published antibody docking protocol from the Bonvin Lab at Utrecht University (30, 33, 34).…”
Section: Methodssupporting
confidence: 54%
“…Previous studies by our team (32, 40, 41) and others (42– 44) have shown the utility of computational screens for understanding the interaction of antibodies with protein targets as well as the identification of therapeutic targets of interest. Combining this capability with protein diffusion, we can increase the throughput of computational drug design through high-performance computing and automated complex evaluation, as we’ve demonstrated in this preliminary work.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation